Rich and Poor
VII, 277 p.
Keywords: This book is concerned with the question of inequality - which points to a major structural problem in intra-national and inter-national respect. It covers the tension between the rich and poor in less developed countries as well as within richer countries in the process of globalisation. The main topics are the scope of disparities between the rich and poor, people's perception of wealth and poverty, and the concomitants of inequality which shape this relationship and influence its socio-economic consequences. In the tradition of social reporting, the book brings together authors from 15 countries, documenting a broad range of the international inequality debate. The results are related to the trends of socio-economic development, to statistical problems of measuring inequality, and to socio-political problems of integrating society in the facing the challenge of dividing forces. The book is of interest for everybody who wants to understand the tensions of modern world.